Full factorial study on specific cutting forces in tangential turning of 42CrMo4 steel shafts - Sztankovics, István (Journal of Production Engineering, 2025)
This study investigates the cutting force characteristics in tangential turning of 42CrMo4 alloy steel using a full factorial experimental design. The objective is to evaluate the influence of cutting speed, feed per revolution, and depth of cut on the tangential (major cutting force), axial (feed-directional force), and radial (thrust force) components, as well as on their corresponding specific cutting forces. The experimental work was conducted on a hard turning center equipped with tangential turning tooling. Cutting forces were measured using a three-component dynamometer. A total of eight experimental setups were defined based on different combinations of cutting parameters. For each setup, all three force components and their corresponding specific cutting forces were determined. Polynomial regression equations were developed to model the influence of the input parameters on the cutting forces. The results indicate that feed per revolution and depth of cut significantly increase the magnitude of all force components, whereas higher cutting speed tends to reduce the major cutting force. The specific cutting forces decrease with increasing chip cross-sectional area, indicating improved cutting efficiency. In contrast, the specific thrust force exhibits a more complex behavior, influenced by chip flow characteristics and radial tool engagement. Overall, this study contributes to a deeper understanding of cutting mechanics in tangential turning and provides a basis for optimizing high-feed machining strategies for hardened steels.